Physical Therapist Recognition and Referral of Individuals With Suspected Lyme Disease. Issue 8 (17th May 2021) - Shea, Jennifer
Abstract: The most commonly reported vector-borne and tick-borne disease in the United States is Lyme disease. Individuals with Lyme disease may present with a wide array of symptoms with resultant musculoskeletal, neurological, and cardiac manifestations that may cause them to seek physical therapist services. The symptoms may develop insidiously and with a variable presentation among individuals. Many persons with Lyme disease do not recall a tick bite or present with an erythema migrans rash, which is considered pathognomonic for the disease. Even if they do, they may fail to associate either with their symptoms, making the diagnosis elusive. It is important to diagnose individuals early in the disease process when antibiotic treatment is most likely to be successful. Physical therapists are in a unique position to recognize the possibility that individuals may have Lyme disease and refer them to another practitioner when appropriate. The purpose of this article is to (1) present an overview of the etiology, incidence, and clinical manifestations of Lyme disease, (2) review evaluation findings that should raise the index of suspicion for Lyme disease, (3) discuss the use of an empirically validated tool for differentiating those with Lyme disease from healthy individuals, (4) discuss the current state of diagnostic testing, and (5) review options for diagnosis and treatment available to individuals for whom referral is recommended.